(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
This article analyzes an ambiguous work “The gentle and the blessed” by a famous Kryvyi Rih author and artist Yuriy Zelenyi. The article investigates the problems of creative person existence and difficulties in the conditions of a complex present day reality. This paper turns to analyzing postmodern elements in revealing the existence of the main character and his relations with the surrounding world. This article focuses on the specific artistic realization of psychological processes and states of the character, his helplessness in the modern world and peculiarities of being perception in different times. Also it identifies the role of colouring and absurd elements in the work.